Penerapan Model Pembelajaran REACT-TPK terhadap Pemahaman Konsep Siswa dengan Kemampuan Awal Berbeda - Wahyu Setyowati; Suhadi Ibnu; Irma Kartika Kusumaningrum (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2020)
Abstract: The purpose of this study is determine the effect of applying REACT-TPK model on students' concept understanding. Two groups of students which were compare had different prior knowledge. The REACT-TPK model is one of the number innovations in chemistry learning model thst was applied in order to improve students’ understanding of chemistry concepts. The model can make students construct concepts actively and also encourages student’s conceptual change from misconceptions to correct understanding. Students' prior knowledge scores were obtained from previous relevant topic test scores. Test instrument was in the form multiple choice questions with closed reason accompanied by CRI and multiple-choice questions with 84,37% content validity and reliability (r) 0.740 for multiple-choice questions with closed-reason and (r) 0.599 for multiple-choice question. Data analysis using two way ANOVA test. The results showed there were differences in concept understanding between experimental and control classes (Sig.2-tailed 0.037), concept understanding between high initial ability students and low initial ability were different (Sig.2-tailed 0.002), but no interaction between learning models with initial level ability toward understanding of students concepts (Sig.2-tailed 0.395).Abstrak: Penelitian ini bertujuan mengetahui efek dari pengimplementasian model REACT-TPK terhadap pemahaman konsep siswa. Dua kelompok siswa yang dibandingkan mempunyai kemampuan awal berbeda. REACT-TPK ialah satu dari sejumlah inovasi pada pembelajaran kimia yang diaplikasikan demi meningkatkan pemahaman konsep kimia siswa karena dapat membuat siswa aktif mengonstruk konsep dan juga mendorong terjadinya perubahan konsepsi siswa dari salah menjadi benar. Nilai kemampuan awal diperoleh dari nilai ulangan harian topik sebelumnya. Instrumen tes berupa soal pilihan ganda beralasan tertutup disertai CRI dan soal pilihan ganda saja. Validitas isi instrumen tes 84,37% serta reliabilitasnya (r) 0,740 untuk soal pilihan ganda beralasan tertutup disertai CRI dan (r) 0,599 untuk soal pilihan ganda. Data dianalisa dengan two way ANOVA test. Hasil dari penelitian yakni ada beda pemahaman konsep diantara siswa yang diimplementasikan model REACT-TPK dan REACT saja (Sig.2-tailed 0,037), ada beda pemahaman konsep diantara siswa berkemampuan awal tinggi serta rendah (Sig.2-tailed 0,002), tetapi tidak ditemukan adanya dampak pengiring antara model pembelajaran dan tingkat kemampuan awal pada pemahaman konsep siswa (Sig.2-tailed 0,395).